Rowing-ramp protocol as a cardiopulmonary exercise test for hemiparetic stroke survivors - D. Maryama Ag. Daud; Melvina, MC (Pusat Perubatan Universiti Kebangsaan Malaysia, 2019)
Cardiopulmonary capacity should be evaluated accurately to determine exercise intolerance and training intensity of stroke survivors before an exercise rehabilitation programme is prescribed. However, no cardiopulmonary exercise test (CPET) is suitable because of the stroke victims’ physical impairment. The aim of this study was to develop and validate a new rowing-ramp protocol as a CPET for stroke survivors. Eleven stroke patients (6 male; 5 female; age, 45 + 16.01 years, performed two incremental exercise tests on a Concept II rowing ergometer to determine the peak oxygen consumption (VO2 peak). Test-retest reliability for VO2 peak, measured 1-week apart, resulted in an intra-class correlation of 0.97 and 0.95, respectively. A linear regression equation was developed to predict the VO2 peak from final stage stroke power. Validity and reliability of the prediction equation were established. The regression equation for predicted VO2 peak was VO2 peak=11.429±+ 0.232 (Final Stage Stroke Power) + 12.63 (F=25.326, p<0.01; R=0.859, R2=0.738). Limits of agreement between predicted and measured VO2 peak were acceptable, with a mean bias of 0.37 ml/kg/min. The validity coefficient (R) was 0.83 (p<0.01) and 0.81 (p<0.01) in both trials. Test-Retest reliability coefficient for predicted VO2 peak 0.95 (p<0.01). The positive relationship between Final Stage Stroke Power and VO2 peak suggests that the Rowing-Ramp protocol could be used to measure VO2 peak of stroke survivors. Additional studies are needed to cross-validate the regression equation using larger sample size, different type and severity of stroke.